(untitled) (Canadian Medical Education Journal, 2023)
Implication Statement We developed a pharmacist-led one-month teaching rotation for medical residents to learn HIV pharmacotherapy. This interprofessional education (IPE) was deemed extremely valuable by postgraduate-year-3 residents who intended to have a future practice in HIV care. The overarching concept of this rotation was for the medical trainee to “become-the-pharmacist”, learning to recognize, prevent, and manage drug-related issues in HIV patients. Pharmacist-led IPE should be considered to support medical training in other highly specialized pharmacotherapeutic areas.